2021
DOI: 10.1177/1073274820986827
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors of Early-Onset Pancreatic Neuroendocrine Tumors

Abstract: Background: The incidence of pancreatic neuroendocrine tumors (PNETs) has increased significantly. The purpose of this study was to analyze the clinical characteristics and prognosis of patients under 50 years old. Methods: Patients with PNETs recorded in the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2015 were analyzed. The clinical characteristics were analyzed by Chi-square test. The Kaplan-Meier method was used to estimate overall survival (OS). Multivariate Cox proportional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
2
3
1
Order By: Relevance
“…These clinical factors were mostly existed in grade 2/3 of PNETs. Namely, the tumors in PNET patients with higher grade tend to show more infiltration into the surrounding tissue, higer N stage, and higher M stage than lower-grade tumors, which was consistently demonstrated in previous studies [ 40 , 41 ]. This might be the reason why advanced histologic grade commonly indicate a poor prognosis of PNETs [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…These clinical factors were mostly existed in grade 2/3 of PNETs. Namely, the tumors in PNET patients with higher grade tend to show more infiltration into the surrounding tissue, higer N stage, and higher M stage than lower-grade tumors, which was consistently demonstrated in previous studies [ 40 , 41 ]. This might be the reason why advanced histologic grade commonly indicate a poor prognosis of PNETs [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that smaller NF-pNETs also have some malignant potential [21], and aggressive surgery can improve the prognosis of patients [22]. In the study conducted by Shi et al, surgical intervention signi cantly enhanced patient prognosis, resulting in a more than 60% reduction in mortality risk for both younger and older individuals [23]. However, our study did not nd evidence supporting the improvement of survival outcomes in these patients through radiation therapy.…”
Section: Discussioncontrasting
confidence: 67%
“…(18) and Shi et al(19), which also reported a higher proportion of surgical treatments in the young group compared to the elderly. Furthermore, our study found that the proportion of black patients with PNETs was higher among young patients than elderly patients, consistent with the research by Shi et al(19) and Goksu et al(20).Additionally, we observed an upward trend in the incidence rate of PNETs among AYA patients. Similar trends have been reported by Goksu et al (20) and Yadav et al (21), indicating a rising incidence of PNETs among young individuals.…”
mentioning
confidence: 94%